Pertimbangan Amerika Serikat Menjatuhkan Sanksi Countering America's Adversaries Through Sanction Act (CAATSA) ke Turki Tahun 2020 - Hasnita, Hasnita; Yusra, Muhammad; Dermawan, Rifki (Palito, 2024)
This research aims to explain and analyze the reasons behind the United States' considerations before imposing CAATSA sanctions on Turkey in 2020. The issue in this study arises when Turkey, a member of the United States military alliance, decides to engage in military cooperation with Russia concerning the purchase of the Russian S-400 missile system. As a result of this action, the United States issued a policy by excluding Turkey from the F-35 program. This US policy was sufficient to address US concerns about the Russian S-400 missile, which, according to the United States, could jeopardize their F-35 system. Considering Turkey's presence as a crucial part of the US alliance is important to counter Russian influence in the Middle East, especially in the Syrian conflict, in addition to the strained US-Turkey relations at the time. However, in 2020, the United States still imposed CAATSA sanctions on Turkey regarding the S-400 cooperation. Through the conceptual framework of Paul R. Viotti and Mark V. Kauppi, namely National Security Policy, which explains that there are four variables that influence a country's foreign policy formulation: National Interest, Threats, Opportunities, and Capabilities. Through this framework, we will explain the considerations made by the United States in imposing CAATSA sanctions on Turkey in 2020 using these four variables, allowing the author to analyze the rational reasons behind the US decision to sanction Turkey. This research employs a qualitative research method with a descriptive analysis approach using secondary sources such as official government websites, expert journals, and several books on International Relations theory. The author found that the reasons for the US imposing CAATSA sanctions on Turkey include its national interests in the Middle East, the threat posed by Russia, the opportune timing for imposing sanctions as CAATSA had just been enacted into law, and the high capability of the US as a superpower to impose sanctions on its allies. Kata Kunci: United States, CAATSA, Foreign Policy, S-400 Cooperation, Turkey, F-35